The semantic crisis of Life in the relationship between oriental studies and jurisprudence With a look at the concept of "Islamic law" in the thought of joseph Schacht - Mohammad Reza Mohammadi; seyyed Mohammad Taqi chawoshi; hadi tahan nazif (حکمت اسرا)
For a long time, "Islamic law" has been associated with the language of Muslims and Iranians. However, it seems that there are important differences between "Islamic law" and jurisprudence, "Jurisprudence", "law" and "Islamic law" in addition to implying three different knowledge, also refer to three different designs of the quality of organization of legal institutions and of course the quality of human presence in the world. "Islamic law" can be used to refer to the legal system in contemporary Iran and some Muslim countries. However, this plan faces challenges in planning and organizing the social system. It seems that the root of these challenges goes back to crises in this project itself. What crises is "Islamic law" involved in? The present text has tried to address this question with a qualitative method. The project of "Islamic Law" can be followed in several discourses. One of these is the discourse of Orientalists. It seems that there are two critical points in this plan; Firstly, from the point of view of the knowledge in which "Islamic law" was born, jurisprudence is a pre-legal matter and does not have an independent realization and its presence is undecided; Secondly, "Islamic law" is suffering from a crisis of meaning. In Orientalist thought such as Shakht, jurisprudence is separated from the word and is considered as a purely historical and partial truth. When Islamic law loses its connection with the word, it does not speak about the basic questions of human life .